¿Grupoterapia deliberativa?: diálogo y sentido en la experiencia del dolor crónico y los trastornos afectivos Deliberative Group Therapy?: Constructing Meaning through Dialogue in Chronic Pain and Affective Disorders (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Currently, many individuals who seek care at specialized pain management units are not only looking for answers to their condition, but also for support in coping with the distress caused by chronic pain and associated affective disorders—conditions that impact their autonomy, interpersonal relationships, occupational identity, and overall quality of life. This study presents the benefits of participation in Deliberative Group Therapy, a space oriented toward dialogue and the shared construction of meaning in relation to the experience of pain. Drawing on the experiences of multiple participants, this study offers an in-depth analysis of a single case of the aforementioned therapeutic intervention.
Keywords: chronic pain; deliberation; helping relationship; occupational therapy; psychiatry; social support; affective disorders.